Dual-Band 28/38 GHz Inverted-F Array Antenna for Fifth Generation Mobile Applications - Mustapha El Halaoui (Proceedings, 2020)
The development of 5G (fifth generation) mobile communication systems was initiated to meet the expected need for higher data rates. In this article, a new 28/38 GHz dual-band “inverted-F” array antenna for 5G applications is proposed. This antenna can be integrated in OLEDs (Organic Light Emitting Diodes) panels which can be used both for lighting or display. This 5G antenna, composed of 32 elements, has the advantage of a dual-band and compact structure. Each element of the array antenna has the shape of an “inverted-F” antenna. This array antenna can cover the 28 GHz band (27.94–28.83 GHz) and the 38 GHz band (37.97–38.96 GHz) with mutual coupling between the elements less than −35 dB. The characteristics of the end fire radiation beams were obtained by employing an array of 32 “inverted-F” antenna elements on the upper and lower portions of the PCB (Printed Circuit Board). The suggested design has a gain of approximately 16.52 dB at 28.38 GHz and 15.35 dB at 38.49 GHz, which is suitable for 5G mobile communications.